2013
DOI: 10.1021/ic402124s
|View full text |Cite
|
Sign up to set email alerts
|

XRD Monitoring of α Self-Irradiation in Uranium–Americium Mixed Oxides

Abstract: The structural evolution under (241)Am self-irradiation of U(1-x)Am(x)O(2±δ) transmutation fuels (with x ≤ 0.5) was studied by X-ray diffraction (XRD). Samples first underwent a preliminary heat treatment performed under a reducing atmosphere (Ar/H2(4%)) aiming to recover the previously accumulated structural defects. Over all measurements (carried out over up to a full year and for integrated doses up to 1.5 × 10(18) α-decay events·g(-1)), only fluorite U(1-x)Am(x)O(2±δ) solid solutions were observed. Within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 65 publications
8
39
1
Order By: Relevance
“…The coexistence of these two phases can be explained by a low oxidation kinetic at RT, as was previously reported. 32 Oxidation process starts from the surface of the particles to the bulk, as illustrated by the minor contribution of the smaller-lattice-parameter phase corresponding to the oxidized phase. A new diagram was recorded after 3 days of reoxidation, on another pellet fabricated with the same process.…”
Section: In Situ Xrd Resultsmentioning
confidence: 99%
“…The coexistence of these two phases can be explained by a low oxidation kinetic at RT, as was previously reported. 32 Oxidation process starts from the surface of the particles to the bulk, as illustrated by the minor contribution of the smaller-lattice-parameter phase corresponding to the oxidized phase. A new diagram was recorded after 3 days of reoxidation, on another pellet fabricated with the same process.…”
Section: In Situ Xrd Resultsmentioning
confidence: 99%
“…However, because a delay of few weeks (for XRD) to a couple of months (for XAS) was inevitable between the laser heating/cooling treatments and the post-melting material characterisation, the samples underwent some self-irradiation damage, notably those with the highest Am content. This could be viewed as a partial explanation for the complex phase splitting and higher O/M ratio observed in the U 0.8 Am 0.2 O 2+d sample as several studies have shown that a-selfirradiation-induced structural effects on (U, Am)O 2 compounds are limited to lattice swelling reaching up to 0.8 vol.% and a small structural disorder increase [45,46,[52][53][54].…”
Section: Tablementioning
confidence: 90%
“…1. All three sintered samples exhibit a single fluorite-type phase whose lattice parameters are summarized in Table 2 with values corrected for selfirradiation effects (based on data reported by Horlait et al [26]). Close initial (i.e.…”
Section: Xrpdmentioning
confidence: 99%